Effectiveness of Garden Revitalization for Communication and Healthy Activities of The Elderly in Tresna Werdha, Lampung - Suharti, Bangun; Ulhaq, Abdullah Wildan; Ulhaq, Salsabila Nur (Jurnal Intelek Insan Cendikia, 2024)
There are several concerns about PSLU Tresna Werdha Lampung. Firstly, the elderly are generally regarded as people who are not cared for, set aside because they are no longer able to keep up with the dynamics of social life in society. Secondly, the garden in this Tresna Werdha orphanage has long been neglected and not well maintained, whose maintenance can involve the elderly who are treated here. Third, the elderly do not have joint activities, as a place to channel their hobbies and increase their sense of belonging to the nursing home facilities where they are cared for and fostered. Based on the situation above, this research was conducted to determine the effectiveness of the revitalisation of the ‘Tresna’ park for improving health communication and healthy activities of the elderly at PSLU Tresna Werdha Lampung. The data in this study were obtained through interviews with informants, field observations and documentation of elderly activities at the Tresna Werdha home, Natar, South Lampung. This research proves that, by revitalising the ‘Tresna’ mini park located in the nursing home, it can improve health communication and healthy activities for the elderly. These healthy activities involve physical, social and mental health aspects of the elderly. These healthy activities include: communicating with each other healthily about small problems in the garden, happy with the social structure as the person in charge of the garden, sharing tasks according to their respective duties, caring for the garden and pets in an integrated manner. The elderly are also motivated to care for and utilise herbs in the garden to overcome their health problems.